2020
DOI: 10.1159/000505567
|View full text |Cite
|
Sign up to set email alerts
|

A tRial Evaluating Mid Cut-Off Value Membrane Clearance of Albumin and Light Chains in HemoDialysis Patients: A Safety Device Study

Abstract: Background: A new class of dialysis membrane, the mid cutoff (MCO) dialyzer, has been developed to improve the clearance of uremic toxins in hemodialysis (HD). The a tRial Evaluating Mid cutOff Value membrane clearance of Albumin and Light chains in HemoDialysis patients (REMOVAL-HD) study aimed to determine if regular use of MCO dialyzer was safe and specifically did not result in a significant loss of albumin. Methods: This investigator initiated, crossover, longitudinal , device study was conducted across 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 21 publications
7
58
2
Order By: Relevance
“…Uniformly with our findings, two other recent trials de­monstrated a reduction in the concentration of FLC [28, 35]. One of the studies was similar in design to ours: a randomized, open-label, cross-over study, with 40 patients who were divided to carry out 3 months of MCO-HD followed by 3 months of HF-HD, or vice versa [35].…”
Section: Clinical Experience With Mco Membranesupporting
confidence: 85%
See 4 more Smart Citations
“…Uniformly with our findings, two other recent trials de­monstrated a reduction in the concentration of FLC [28, 35]. One of the studies was similar in design to ours: a randomized, open-label, cross-over study, with 40 patients who were divided to carry out 3 months of MCO-HD followed by 3 months of HF-HD, or vice versa [35].…”
Section: Clinical Experience With Mco Membranesupporting
confidence: 85%
“…Extracorporeal techniques can be helpful in the modulation of an immune dysregulated response, both in the severely ill and in the chronic HD patient. Recent clinical trials demonstrated consistent results regarding the application of MCO membranes in patients on maintenance HD [28, 31, 35]. These trials confirmed long-term safety and long-term sustained reductions in the concentrations of large uremic toxins, cytokines, and FLC with MCO-HD when compared to conventional HF-HD.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations